English Department Students’ Experience and Opinions on the Use of Podcast for Learning English Independently - Alvi Rosyidah; Furaidah Furaidah; Nunung Suryati (Universitas Negeri Malang, 2021)
Abstract: This study examined ELE students’ experience and opinions on the use of podcasts for learning English independently. It employed surveys as the research method with a questionnaire as the research instrument. The respondents were 212 students of English Language Education major of Universitas Negeri Malang from the cohorts of 2016-2020. The data gathered from the questionnaire were then analyzed by using frequency distribution, and accumulated in the form of percentages denoting every student’s responses for every item. From the percentages, the numbers were then elaborated into sentences with descriptive analysis. The finding showed that most of the students used podcasts more for improving their language systems, speaking and listening skills, rather than for improving their reading and writing skills. The majority of the respondents also held positive opinions towards the use of podcasts as an adequate complementary tool for learning English independently. The characteristics of podcasts that the students found most appealing were due to its portability, simplicity, enjoyability, accessibility, and the various range of interesting topics to learn. Also, it featured a concise wrap of information, meaningful context, and provided a chance to listen to authentic materials provided by native speakers. Keywords: students’ experience, students’ opinions, podcast, learning English, independent learning Abstrak: Penelitian ini didasari oleh konflik psikologis karena peristiwa kecelakaan yang dialami Tokoh Terry sehingga menyebabkan trauma. Kasus tersebut tercermin dalam sebuah novel yang berjudul Janji Pelangi karya Fahrul Khakim. Tujuan dari penelitian ini adalah untuk mendeskripsikan tipe trauma, respon trauma, dan struktur kepribadian id, ego, dan superego tokoh Terry. Metode dalam penelitian ini adalah kualitatif dengan jenis penelitian analisis teks yang dikaji melalui psikologi sastra. Teknik pengumpulan data dilakukan dengan cara membaca, menyimak, dan mencatat. Hasil penelitian ini meliputi tiga hal, pertama adalah tipe trauma ada 8 data yang terbagi atas empat tipe, yaitu trauma situasional karena kecelakaan, trauma perkembangan karena penolakan teman sebaya, trauma intrapsikis karena kecemasan, dan trauma eksistensial karena kekurangberartian. Kedua, respons trauma ada 44 data yang terbagi menjadi empat respons, yaitu respons emosional yang berindikator malu, bergejolak, dan panik. Selanjutnya, respons kognitif yang berindikator berpikir tak sanggup, merepotkan, dan mimpi buruk. Kemudian, respons perilaku berindikator mengurung diri, dan nafsu makan menurun. Lalu, respons fisiologis berindikator pucat pasi, wajah pilu, dan kurus. Ketiga, terdapat 56 data yang masing-masing sebagai berikut, Id memiliki subaspek yang meliputi naluri kehidupan, naluri kematian, dan kecemasan. Berikutnya, ego mempunyai sub aspek represi, projeksi, dan regresi. Kemudian, superego meliputi moralitas dan mengejar kesempurnaan. Kata kunci: pengalaman dan pendapat mahasiswa, podcast, belajar Bahasa Inggris, pembelajaran mandiri